Impactos da pandemia em empresas do setor da indústria de alimentos por meio da análise econômico-financeira - Loss, Carlos Eduardo Strasser (2022)
The present work aims to analyze the financial statements of three companies in the food industry sector (Anaconda S.A., Tondo S.A. and Moinho do Nordeste S.A.) and to highlight the consequences caused by the COVID-19 pandemic in the organizations studied. For the elaboration of this work, a descriptive research was carried out, with a technical procedure qualified as documentary and case study, with a quantitative and qualitative character. Data were collected from the entities' financial statements in two different periods: the period prior to the pandemic, which comprised the years 2017 to 2019, and the pandemic period, which refers to the years 2020 and 2021. After data collection , the financial statements were analyzed using the vertical and horizontal analysis method and economic-financial indicators of liquidity, indebtedness, profitability and turnover, in addition to applying the Kanitz insolvency factor. Through the analyses, it was noted that all companies obtained most of their economic and financial indicators with a more satisfactory result during the pandemic period, in addition to proving to be solvent and stable during all the years analyzed. By comparing the results between the three companies, it was observed that Anaconda S.A. obtained an economic and financial advantage over Tondo S.A. and Moinho do Nordeste S.A. in both analyzed periods.